The Impact of Government and Enterprise Management Modes on the Sustainable Development of the China Construction Industry: The Mediating Role of Innovation and the Moderating Role of Economic Development - Guo, ZhengLong; Liu, Han (Technium Social Sciences Journal, 2025)
Over the past several years, following its attainment of peak performance, China's construction industry has exhibited a notable trend of deceleration and decline in its developmental momentum. Simultaneously, the sustainable development (SD) of this sector has emerged as a pivotal area of concern for numerous nations and industries alike. Consequently, it becomes imperative to conduct a comprehensive analysis of the factors influencing SD within the construction industry from a business management lens, with the aim of elucidating strategies to uphold and augment its SD amidst industry downturns. Given China's vast territorial expanse and the pronounced regional disparities in economic, cultural, and policy contexts, the sustainable development of its construction industry shaped by these multifarious factors, holds substantial merit for rigorous exploration. This study meticulously selects data from esteemed Chinese databases and employs regression analysis to scrutinize the ramifications of China's recent policies and corporate management paradigms on the SD of the construction industry, whilst, it integrates an examination of the mediatory function of industry innovation and the moderating influence of economic conditions within the impact pathway.